Baseline survey of common bean production constraints in selected villages of Babati district, Tanzania - Abang, Mathew M.; Arinaitwe, Warren; Rubyogo, Jean-Claude; Binagwa, Papias; Kadege, Edith (International Center for Tropical Agriculture, 2013)
A survey was conducted to assess common bean production constraints especially pests &diseases in three villages during March, 2013. Other areas assessed include gender profiles, land allocation issues, cropping patterns, abiotic stress levels and perception towards integrated pest and disease management (IPDM) options. Also, symptomatic leaves and pods were collected for identification of diseases. In total, 30 respondents were interviewed of which over 70% were males with average land size of 2.9acres. Average land allocated to beans was 1.87 acres with a 63.3% of farmers practicing intercropping. Most (40%) farmers used own saved seed and used both random and row planting. The perception towards use of IPDM options to manage pests and diseases was generally weak to moderate. Among the pests and diseases observed, aphids and white flies were the most common pests while common bacterial blight, angular leaf spot, anthracnose, ascochyta blight and viral diseases were the most common diseases. The incidence and severity of pests and diseases varied between sites but a slight to no variation trend was observed between participating and non‐participating farmers.